Avaliação da resistência à fadiga de contato de ferro fundido nodular nitretado por plasma - Wollmann, Daniela (2012)
This work presents a study on the contact fatigue resistance of a plasma nitrided ductile cast iron. The experiments were carried out using a ball-on-washer machine. Specimens were machined from a perlitic ductile cast iron bar, and then quenched and tempered. After surface grinding and polishing, the specimens were divided into three groups a) the first group was tested after the described process, which means as quenched and tempered; b) the second group was plasma nitridedat 400 °C for 8 hours; c) the third one was plasma nitrided as previously described and submitted to a diffusion process at 400 °C for 16 hours in order to extend the hardened zone and to dissolve any trace of compound layer within the microstructure. Surface hardness, hardness profiles, phase analyses and residual stress measurements by X-ray diffraction, surface roughness and optical and scanning electron microscopy were applied to characterize the surfaces during different stages of this work. Rolling contact fatigue tests were conducted at a maximum contact pressure of 3.6 GPa under flood lubrication. Weibull analysis showed that fatigue lives of plasma nitrided specimens were approximately five times shorter than those just quenched and tempered, even though the residual stress measurements showed significantly higher compressive stresses for the nitride conditions. The lower fatigue life for the plasma nitrided specimens was attributed to the lower matrix hardness and to a failure mechanism distinct from the classical rolling contact fatigue mechanisms, showed by surface analisis.